Essays in Labor Economics: Evidence from Danish Micro Data - Esben Anton Schultz (Copenhagen Business School (CBS), 2012)
This thesis consists of four empirical essays within the broad field of modern labor economics. All four essays are self-contained and can be read independently of the others. Chapter 1 investigates the distinct effects on information technology and communication technology on firm's skill demand. Chapter 2 studies whether the observed wage gab between majors in human arts and other fields are caused by their education per se or by selection. Chapter 3 examines taxable income responses to variation in marginal tax rates. Chapter 4 analyzes the effect of income taxation on the international migration of top earners. Each chapter provides an independent and separate analytical contribution to their specific field.
hdl:10398/8442
Keywords: 650